Spatial Analysis of the Influence of Rainfall and Humidity Factors on the Event of Dengue Hemoraghic Fever Cases at West Java Province in 2019 - Fadhilah Rasya; Jerikco Lewiyonah; Mitha Theresia; Ghina Labibah; Sinta Ainun Rahma; Haikal Fikry; Mida Arafina Nurdita; Amelia Putri; Kharizqamir Dwitili Elipen (UHAMKA Press, 2020)
Background: The number of cases of Dengue Hemorrhagic Fever (DHF) in West Java Province in 2019 was approximately 8500 cases that occurred in various regencies and cities with a morbidity rate of 46.72 per 100,000 population and a Case Fatality Rate of 0.41. Dengue Hemorrhagic Fever (DHF) is a serious problem in West Java Province which has a population of 49.94 million people.Method: This study aims to determine the results of spatial analysis in the incidence of Dengue Hemorrhagic Fever (DHF) in West Java Province. This type of research uses an ecological study design.Results: The results of statistical tests using the Chi-Square Test showed that there was no significant correlation between the variables of rainfall and humidity with dengue cases in West Java Province in 2019 (p value = 0.93 for rainfall data and p value = 0.Conclusion: The highest number of dengue cases in West Java Province in 2019 was in Bandung Regency, which was 1783 cases. From the map analysis, it can be seen that of the 25 regions in West Java there are 16 areas that are categorized as high humidity, 6 areas are categorized as medium humidity, and 3 areas are categorized as low humidity. Areas that have very high rainfall are in the Depok area and Bogor.